1992
DOI: 10.1016/0014-5793(92)80378-t
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of metalloprotease steady‐state mRNA levels by IL‐1 and FGF in rabbit articular chondrocytes

Abstract: The expression of collagenase and stromelysin is believed to be coordinately regulated. In this report however, we provide evidence that suggests subtle differences may exist in the early events of the induction of these enzyme, Rabbit articular chondrocytes treated with int¢rleukin-I, either alone or in combination with fibroblast growth factor, accumulated steady-state mRNA levels for both the enzymes, with the latter treatment more effective in inducing greater levels and within a .~horter time, Further, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Apart from TGF , a range of other growth factors can stimulate chondrocyte synthetic activity, including IGF-1 (insulin-like growth factor), BMPs (bone morphogenetic proteins), bFGF (basic fibroblast growth factor), and PDGF (platelet derived growth factor). However, the latter two growth factors have also been shown to be involved in catabolic processes in cartilage [55,56]. More recently it as been demonstrated that FGF-18 can stimulate cartilage-specific matrix synthesis in mature articular chondrocytes [57,58].…”
Section: C Anabolic Cytokinesmentioning
confidence: 98%
“…Apart from TGF , a range of other growth factors can stimulate chondrocyte synthetic activity, including IGF-1 (insulin-like growth factor), BMPs (bone morphogenetic proteins), bFGF (basic fibroblast growth factor), and PDGF (platelet derived growth factor). However, the latter two growth factors have also been shown to be involved in catabolic processes in cartilage [55,56]. More recently it as been demonstrated that FGF-18 can stimulate cartilage-specific matrix synthesis in mature articular chondrocytes [57,58].…”
Section: C Anabolic Cytokinesmentioning
confidence: 98%
“…These cells make up less than 5% of the tissue volume in adult animals 3 but are responsible for organization of the cartilage through synthesis and degradation of matrix components in response to molecular, electrical, and mechanical stimuli. [4][5][6] Unfortunately, chondrocytes have a limited ability to repair cartilage defects, which are manifested in diseases such as osteoarthritis, in which cracks and fibrillations in the surface of the tissue can progress to full-thickness cartilage defects, resulting in severe joint pain. 7 Cartilage tissue engineering is a promising technology for repairing or regenerating articular cartilage in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor was also reported to have IL-1 -induced collagenase-production-enhancing activity in periosteal explants from rabbit calvariae (Zee et al, 1993), but purified epidermal growth factor did not have such activity in our rat synovial fibroblasts. Some authors have reported that fibroblast growth factor (FGF) markedly enhanced IL-I-induced production of PGE,, collagenase or other proteases in chondrocytes (Phadke, 1987;Bandara et al, 1989;Chandrasekhar and Harvey, 1992). In our system using cultured synovial cells, recombinant FGF showed a significant enhancing activity.…”
Section: Discussionmentioning
confidence: 99%